2007
DOI: 10.1557/jmr.2007.0184
|View full text |Cite
|
Sign up to set email alerts
|

X-ray reflectometry and spectroscopic ellipsometry characterization of Al2O3 atomic layer deposition on HF-last and NH3 plasma pretreatment Si substrates

Abstract: Al 2 O 3 films are grown by atomic layer deposition (ALD) using trimethylaluminum and water as precursors on HF-last and NH 3 plasma pretreatment Si substrates. The thickness, surface roughness, and density of Al 2 O 3 films as well as the nature of their interlayers with Si substrates are characterized by x-ray reflectivity and spectroscopic ellipsometry techniques. The growth rates of Al 2 O 3 films are 1.1 Å/cycle and 1.3 Å/cycle, respectively, on HF-last and NH 3 -plasma-nitrided surfaces. Al 2 O 3 layer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Comparing the density profiles of a-Al 2 O 3 on QFS-graphene/6H-SiC(0001) (Figure B) and on Si (Figure A), one learns that regardless of the deposition protocol, the nature of the density changes is entirely different. In the case of a-Al 2 O 3 on silicon, the oxide density is primarily constant and close to the value expected for amorphous Al 2 O 3 deposited at 300 °C (2.90–3.15 g/cm 3 ) . In the case of a-Al 2 O 3 on QFS-graphene/6H-SiC(0001), a systematic increase in the oxide density is noticeable as the layer thickness increases.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Comparing the density profiles of a-Al 2 O 3 on QFS-graphene/6H-SiC(0001) (Figure B) and on Si (Figure A), one learns that regardless of the deposition protocol, the nature of the density changes is entirely different. In the case of a-Al 2 O 3 on silicon, the oxide density is primarily constant and close to the value expected for amorphous Al 2 O 3 deposited at 300 °C (2.90–3.15 g/cm 3 ) . In the case of a-Al 2 O 3 on QFS-graphene/6H-SiC(0001), a systematic increase in the oxide density is noticeable as the layer thickness increases.…”
Section: Resultssupporting
confidence: 74%
“…In the case of a-Al 2 O 3 on silicon, the oxide density is primarily constant and close to the value expected for amorphous Al 2 O 3 deposited at 300 °C (2.90−3.15 g/cm 3 ). 45 In the case of a-Al 2 O 3 on QFSgraphene/6H-SiC(0001), a systematic increase in the oxide density is noticeable as the layer thickness increases. This result directly confirms the previous literature reports on the discontinuous growth of a-Al 2 O 3 on graphene on SiC.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The substrate pre-treatment by NH3 or NH3 plasma has shown comparable effects on the reduction of the induction period and the interfacial layer formation (Brewer et al, 2004) (Lu et al, 2007). Brewer et al have used a thermal N2-NH3 pretreatment prior to deposition and have shown an increase in the deposition during the initial steps using infared spectroscopy (Brewer et al, 2004).…”
Section: Challengesmentioning
confidence: 99%
“…Brewer et al have used a thermal N2-NH3 pretreatment prior to deposition and have shown an increase in the deposition during the initial steps using infared spectroscopy (Brewer et al, 2004). Lu et al have performed an ex situ NH3 plasma pre-treatment, which exhibited an increased ALD deposition during the initial steps (Lu et al, 2007). Xu et al have compared Al2O3 films deposited by ALD on Si surfaces pre-treated ex situ by NH3 plasma and long TMA exposures prior to deposition, in terms of thermal and electrical properties (Xu et al, 2006).…”
Section: Challengesmentioning
confidence: 99%